Black star a view of the life and times of Kwame Nkrumah - Davidson, Basil (New York Praeger, 1973)
Prime Minister Kwame Nkrumah seized opportunities to lead the countries of sub-Saharan Africa away from colonialism. In 1957, he became the first Prime Minister of Ghana. By the time he was overthrown in a coup in 1966 most African countries, outside the settler-dominated South, had also achieved independence. ' As a visionary Nkrumah was ahead of his times, with an astute understanding of colonialism that made the twin goals of socialism at home (Ghana) and African unity the abiding principles of his work and life.... Nkrumah's monumental role and place in modern Ghana's history mystifies him as a national hero; Black Star humanizes Nkrumah in important ways, and the reader gains a new understanding of a great man, but still a man.' - From the new Foreword by Emmanuel Kwaku Akyeampong, Professor of History, Harvard University
Includes bibliographical references.
Keywords: Nkrumah, Kwame, 1909-1972. Presidents-Ghana-Biography. Ghana-Politics and government -1957-1979.